Gender and Accounting Education in Ghana - Aboagye, A.A. (University of Ghana, 2016)
The study seeks to examine gender issues associated with accounting and business education in Ghana. Specifically, it seeks to investigate the gender disparities that exists in higher educational institutions providing accounting education. It also determines the growth or decline in accounting majors in Ghana. The study further investigates the reasons for students’ choice of an accounting major, the creative levels as well as personality traits of accounting majors. The Theory of Planned Behaviour and the Holland trait theory are adopted to explain the choice of an accounting major. Additionally, the Gough (1979) inherent creativity scale is used to ascertain the creativity levels of students. A mixed method approach is used. The research strategy is a survey and data is gathered using questionnaires. The sample for the study is 1700 accounting students and seven registrars in seven major universities in Ghana. The usable responses from the questionnaires are 1200 for students and 4 for registrars. The results show that there are gender disparities in favour of males in both accounting and business education. Comparatively, the average Gender Parity Index for the nine-year period is 0.50 and 0.59 for accounting and business studies respectively. The findings indicate a decline in the number of accounting majors. Factors such as job opportunities, job security, broad exposure to business, high future earnings, business people they know, parents, teachers, grades and mathematical background greatly influence students’ choice of an accounting major. The creativity levels of Accounting majors are low. The dominant personality traits possessed by the accounting majors are social according to the Holland theory. The most important referents for males and females are business people they know and parents respectively. This study adds to literature and also suggest the need for gender policies to be instituted in universities offering accounting education. It also suggests the use of better strategies and teaching methods to attract more students into the accounting profession and also boost the creativity levels of stud
Thesis (MPhil.)
Keywords: Accounting; Gender; Education; Ghana